PENGARUH KEMAMPUAN BERFIKIR KRITIS, KECERDASAN ADVERSITAS, DAN EFIKASI DIRI TERHADAP HASIL BELAJAR BIOLOGI - Siti Nur Yasarah; Andi Asmawati Aziz; Yusmina Hala (Guru Membangun, 2023)
This research is an ex post-facto study which aims to describe the effect of critical thinking skills, adversity intelligence, and self-efficacy on the biology learning outcomes of class X IPA students at SMA Negeri in Palopo City, knowing the relationship between critical thinking skills, adversity intelligence, and self-efficacy on student biology learning outcomes partially and the relationship between critical thinking skills and metacognitive awareness through self-efficacy on biology learning outcomes, as well as the relationship simultaneously. The research population is all public high schools in Palopo City in the 2021/2022 academic year. Sampling was done using cluster sampling technique, the clusters in the study were SMAN 1 Palopo City, SMAN 3 Palopo City, SMAN 5 Palopo City, so that a sample of 218 students was obtained. The independent variable in the research is critical thinking ability, the intervening variable is self-efficacy, and the dependent variable is learning outcomes. Data collection techniques using instruments in the form of questionnaires and documentation. Data analysis techniques, namely descriptive and inferential analysis using SPSS version 28.0 for windows. Based on the results of inferential data analysis, this study shows that: (i) the critical thinking skills of students in class X IPA are in the moderate category, the adversity intelligence of students in class X IPA is in the moderate category, the self-efficacy of students in class X IPA is in the medium category, and learning outcomes class X IPA students are in the sufficient category, (ii) critical thinking skills have a positive and significant effect on self-efficacy, (iii) critical thinking skills have a positive and significant effect on biology learning outcomes, (iv) critical thinking skills have a positive and significant effect on results learning biology through self-efficacy, (v) adversity intelligence has a positive and significant effect on self-efficacy, (vi) adversity intelligence has a positive and significant effect on biology learning outcomes, (vii) adversity intelligence has a positive and significant effect on biology learning outcomes through self-efficacy ( viii) critical thinking skills, adversity intelligence and self-efficacy together have a positive and significant effect on biology learning outcomes